2019
DOI: 10.1016/j.gca.2019.09.035
|View full text |Cite
|
Sign up to set email alerts
|

A reassessment of the iron isotope composition of the Moon and its implications for the accretion and differentiation of terrestrial planets

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 139 publications
(278 reference statements)
1
8
0
Order By: Relevance
“…In these contexts, calculations agree that there is no significant Fe isotope fractionation between silicate minerals. This inference is supported by experimental determination of isotopic partitioning (Prissel et al, 2018) and interplanetary comparisons (Poitrasson et al, 2019). However, considering the upper crust formation, our results evidence significant iron isotope fractionation between Fe 2+ -bearing minerals, even with similar Fe-O bond lengths.…”
Section: -Geochemical Implications On Magmatic Differentiationsupporting
confidence: 79%
See 1 more Smart Citation
“…In these contexts, calculations agree that there is no significant Fe isotope fractionation between silicate minerals. This inference is supported by experimental determination of isotopic partitioning (Prissel et al, 2018) and interplanetary comparisons (Poitrasson et al, 2019). However, considering the upper crust formation, our results evidence significant iron isotope fractionation between Fe 2+ -bearing minerals, even with similar Fe-O bond lengths.…”
Section: -Geochemical Implications On Magmatic Differentiationsupporting
confidence: 79%
“…This is a critical parameter of the modeling that calls for a thorough investigation of the melt isotopic properties by first-principles molecular dynamics. Therefore, and although unknowns remain, such as the actual  factors of the evolving silicate melts, this modeling, involving new and self-consistent theoretical mineral Fe isotope fractionation factors to reduce the under-constrained nature of such multi-parametric modeling (Dauphas et al, 2017;Poitrasson et al, 2019), suggests that fractional crystallization is a viable way to interpret the global Fe isotope trend observed among terrestrial igneous rocks (Fig. 7).…”
Section: -Geochemical Implications On Magmatic Differentiationmentioning
confidence: 99%
“…Previous studies observed a bimodal distribution of δ 57 Fe values for lunar low-Ti and high-Ti basalts: higher δ 57 Fe values in high-Ti basalts were attributed to the presence of ilmenite during partial melting (Sossi and Moynier, 2017;Sossi and O'Neill, 2017), which is consistent with experimental studies (Longhi, 1992 and references therein) as well as our Ta/Hf and δ 49 Ti data. However, intra-group variation in δ 57 Fe of low-Ti basalts was not observed (Weyer et al, 2005;Sossi and Moynier, 2017;Poitrasson et al, 2019) as the δ 57 Fe of low-Ti basalts is mainly controlled by fractional crystallisation of olivine and pyroxene, which would preferentially incorporate light Fe isotopes, similar to ilmenite (Δ 57 Fe Ilm-Ol = +0.01 ‰; Sossi and O'Neill, 2017). Thus, δ 49 Ti appear more appropriate to discriminate better between the petrogenetic processes culminating in lunar basalts.…”
Section: Discussionmentioning
confidence: 99%
“…Chromium isotope data are also compiled, since it has been suggested recently that Cr isotope fractionation between the Moon and Earth is a result of evaporative processes (Sossi et al 2018). For this reason, we have also compiled data from Mg and Fe isotopes (Poitrasson et al 2019;Sedaghatpour & Jacobsen 2019;Sossi & Moynier 2017), with similar 50% condensation temperatures as Cr. Finally, we have added Ca isotope data to the excel sheet as a reference for refractory element signatures (Valdes et al 2014).…”
Section: Limitations Within the Lunar Mve Datasetmentioning
confidence: 99%